Construction and validation of a nomogram based on N6‐Methylandenosine‐related lncRNAs for predicting the prognosis of non‐small cell lung cancer patients - Wenjing Xiao; Wei Geng; Juanjuan Xu; Qi Huang; Jinshuo Fan; Qi Tan; Zhengrong Yin; Yumei Li; Guanghai Yang; Yang Jin (Cancer Medicine, 2023)
Abstract Background The N6‐methyladenosine (m6A) can modify long non‐coding RNAs (lncRNAs), thereby influencing a wide array of biological functions. However, the prognosis of m6A‐related lncRNAs (m6ARLncRNAs) in non‐small cell lung cancer (NSCLC) remains largely unknown. Methods Pearson correlation analysis was used to identify m6ARLncRNAs in 1835 NSCLC patients and with the condition (|Pearson R| > 0.4 and p < 0.001). Univariant Cox regression analysis was conducted to explore the prognostic m6ARLncRNAs. We filtered prognostic m6ARLncRNAs by LASSO regression and multivariate Cox proportional hazard regression to construct and validate an m6ARLncRNAs signature (m6ARLncSig). We analyzed the correlation between the m6ARLncSig score and clinical features, immune microenvironment, tumor mutation burden, and therapeutic sensitivity and conducted independence and clinical stratification analysis. Finally, we established and validated a nomogram for prognosis prediction in NSCLC patients. Results Forty‐one m6ARLncRNAs were identified as prognostic lncRNAs, and 12 m6ARLncRNAs were selected to construct m6ARLncSig in the TCGA training dataset. The m6ARLncSig was further validated in the testing dataset, GSE31210, GSE37745, GSE30219, and our NSCLC samples. In terms of m6ARLncSig, NSCLC patients were divided into high‐ and low‐risk groups, with significantly different overall survival (OS), clinical features (age, sex, and tumor stage), tumor‐infiltrating immune cells, chemotherapeutic sensitivity, radiotherapeutic response, and biological pathways. Moreover, m6ARLncSig independently predicted the OS of NSCLC patients. Finally, the robustness and clinical practicability for predicting NSCLC patient prognosis was improved by constructing a nomogram containing the m6ARLncSig, age, gender, and tumor stage. Conclusions Our study demonstrated that m6ARLncSig could act as a potential biomarker for evaluating the prognosis and therapeutic efficacy in NSCLC patients.